Tracheal Tumors: Clinical Practice Guidelines for Palliative Treatment and Follow-Up - Piórek, Aleksandra; Płużański, Adam; Knetki-Wróblewska, Magdalena; Winiarczyk, Kinga; Tabor, Sylwia; Kowalski, Dariusz M.; Krzakowski, Maciej (Oncology Reviews, 2024)
A substantial portion of patients with advanced cancer cannot be cured, regardless of the therapeutic methods employed. Hence, rational palliative causal treatment becomes crucial. Representative studies specifically addressing the exclusive palliative treatment of patients diagnosed with tracheal cancers have not been identified. In most studies, patients treated palliatively constituted a subset of the overall evaluated group. A thorough literature review was conducted, focusing on three types of palliative treatment: palliative radiotherapy, palliative surgical procedures, and systemic treatment for advanced disease. This review uniquely fills a significant gap in the existing literature by providing the first comprehensive and updated clinical practice guidelines specifically focused on the palliative treatment of tracheal tumors. The proposed guidelines emphasize the unique clinical challenges and treatment strategies pertinent to palliative care in tracheal tumors, which are not adequately covered in existing guidelines for other thoracic malignancies.